Lomber disk hernilerinde transforaminal endoskopik diskektomi - İlaslan, Hakan; Aslan, Ahmet; Koç, Ömer Nadir; Dalkılıç, Türker; Naderi, Sait (Journal of the Neurological Sciences, 2010)
Özet Endoskopik disk cerrahisi son yıllarda belirgin gelişme göstermiş, günümüzdetransforaminal yolla, seçilmiş olgularda diskektomi yapılabilmektedir. Bu çalışmanın amacılomber disk hernisi nedeni ile transforaminal endoskopik diskektomi geçiren hastalar eldeedilen ilk sonuçları gözden geçirmektir.Yöntem 2008 - 2009 tarihleri arasında transforaminal endoskopik diskektomi geçirenhastaların dosyaları geriye dönük olarak taranmıştır. Olgularda demografik verilerin yanı sıra,preoperatif ve postoperatif ağrı şiddetleri VAS skoruna göre, erken ve 6 aylık memnuniyetdurumları ise Macnab kriterlerine göre incelenmiştir.Bulgular Opere edilen 21 hastanın 13'ü erkek, 8'i kadındı. Olguların temel yakınması siyataljiidi. Olguların üçünde ağrının yanı sıra kuvvet kaybı vardı. Preoperatif ortalama VAS değeri8.47 idi. Olguların dördünde disk hernisi L3-4, 15'i L4-5, ikisi L5-S1 seviyesinde idi.Olguların 17'sinde disk hernisi foraminal veya foraminal + paramedian, dördünde uzak lateralyerleşimli idi. Erken postoperatif dönemde olguların 18'i işlemden memnun kalmış (%85),VAS değerleri 2.11'e düşmüştür. On sekiz olgunun altı aylık izlemlerinde, üç olgununağrılarının tekrarlamış, bu nedenle bu üç olguya selektif kök blokajı yapılmıştr. Buna göre 6aylık izlemde memnuniyet oranı %71'e düşmüş, 18 olgunun VAS değeri 2.4 olarakbelirlenmiştir.Tartışma Transforaminal endoskopik diskektomi seçilmiş olgularda iyi sonuç vermekte vegüvenilir bulunmuştur. Bununla beraber hastanın işlem sırasında kooperasyonu ile cerrahındeneyimi, diskin yüksekliği ve yerleşim yeri, işlemin başarısını doğrudan etkilemektedir.

Objective Endoscopic lumbar discectomy has been popular in recent years. Currently transforaminal endoscopic discectomy is performed successfully in selected cases. The aim of this study is to review the preliminary results of transforaminal endoscopic discectomy procedure.Methods The charts of cases who underwent transforaminal endoscopic discectomy in 20082009 were reviewed retrospectively. The demographic data, the preoperative and postoperative pain severity (based on VAS scores), and postoperative 1 and 6th month satisfaction rates (based on Macnab classification) were analysed.Results There were 21 cases (13 male, and 8 female). The main symptom was sciatica. There was motor deficit in three cases. The preoperative mean VAS score was 8.47. The disc herniation was located in L3-4 in four cases, in L4-5 in 15 cases, and in L5-S1 in two cases. The lumbar disc herniation was foraminal or foraminal + paramedian in 17 cases, and extraforaminal (far lateral) in 4 cases. Eighteen cases (85%) was satisfied from the procedure in early postoperative period, and the mean VAS score reduced to 2.1. Three out of 18 cases who were well in early postoperative period reported light sciatica and suffered transforaminal selective nevre root block. The satisfaction rate reduced to 71% in 6th month postoperatively. The VAS sacore was reported to be 2.4 at 6th month.Conclusion Transforaminal endoscopic discectomy was found to be successful and safe in selected cases. However, cooperation with patient during the surgery, the height of disc, the location of disc, and the experience of the surgeon affect the success rate after the surgery.
Transforaminal endoscopic discectomy in lumbar disc herniations
Keywords: Endoskopik Diskektomi; Lomber Disk Hernisi; Transforaminal; Endoscopic Discectomy; Lumbar Disc Herniation; Transforaminal